2012
DOI: 10.1063/1.3692807
|View full text |Cite
|
Sign up to set email alerts
|

New high-pressure phase and equation of state of Ce2Zr2O8

Abstract: Pressure effects on phase equilibria and solid solubility in MgO-Y2O3 nanocomposites J. Appl. Phys. 111, 053506 (2012) Effects of high pressure on the magnetism of ErCo2 J. Appl. Phys. 111, 07E132 (2012) Effect of pressure loading rate on the crystallographic texture of NdFeB nanocrystalline magnets J. Appl. Phys. 111, 07A717 (2012) A fresh look at dense hydrogen under pressure. III. Two competing effects and the resulting intra-molecular H-H separation in solid hydrogen under pressure J. Chem. Phys. 136, 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…The present pressure-volume data have been analyzed using a third-order Birch-Murnaghan (BM) EOS 44 by the EOSFit7 software. 49 If the data obtained from the 165 -177 GPa) indicates that this oxide is less compressible than zircon-type CeVO4 (B0 = 133 GPa) 51 and monazite-type CePO4 (B0 = 110 GPa) 52 , but more compressible than fluorite-type CeO2 (B0 = 220 GPa) 53 and Ce2Zr2O8 (214 GPa) 23 13 It has been observed that the bulk modulus of various oxides can be explained in terms of local compressibilities. 54 -58 In order to further understand the structural evolution and to compare with the general trend of phase transition the compressibility of Ce-O and Sc-O bonds is investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The present pressure-volume data have been analyzed using a third-order Birch-Murnaghan (BM) EOS 44 by the EOSFit7 software. 49 If the data obtained from the 165 -177 GPa) indicates that this oxide is less compressible than zircon-type CeVO4 (B0 = 133 GPa) 51 and monazite-type CePO4 (B0 = 110 GPa) 52 , but more compressible than fluorite-type CeO2 (B0 = 220 GPa) 53 and Ce2Zr2O8 (214 GPa) 23 13 It has been observed that the bulk modulus of various oxides can be explained in terms of local compressibilities. 54 -58 In order to further understand the structural evolution and to compare with the general trend of phase transition the compressibility of Ce-O and Sc-O bonds is investigated.…”
Section: Resultsmentioning
confidence: 99%
“…XRD pattern of all catalysts show six distinct peaks at 29.1, 33.6, 48.5, 57.6, 71.2 and 78.5 deg corresponds to (111), (200), (220), (311), (400) and (331) facets, respectively, suggesting the fluorite structure . The catalyst preparation method with glycine in stoichiometric ratio was used in literature for synthesis of pyrochlore, wherein the ordering of cation resulting in formation of pyrochlore; however, in the present case, no peaks were observed for pyrochlore. Thus from XRD, it might be concluded that the samples have been stabilized in fluorite structure.…”
Section: Resultsmentioning
confidence: 58%
“…According to group theory analysis and high‐pressure (10–42 GPa) experimental studies, structural distortion in pyrochlore structure of CSZ shows many Raman active modes . Raman active lines for pyrochlore structure expected to have six modes ( A 1g , E g and 4 F 2g ), but experimental data reported in the literature show more than six lines .…”
Section: Resultsmentioning
confidence: 99%
“…11,38 According to group theory analysis and high-pressure (10-42 GPa) experimental studies, structural distortion in pyrochlore structure of CSZ shows many Raman active modes. 39,40 Raman active lines for pyrochlore structure expected to have six modes (A 1g , E g and 4F 2g ), but experimental data reported in the literature show more than six lines. 41,42 In the present experimental studies, after exposure to strong shock wave in presence of Ar test gas, show several peaks at 438, 470, 557, 600, 621, 638 cm À1 , and a broad peak at 309 cm À1 due to Zr ion in CSZ sample as shown in Fig.…”
Section: (4) Raman Studiesmentioning
confidence: 99%